Meiofauna promotes litter decomposition in stream ecosystems depending on leaf species. Issue 17 (3rd August 2020) - Wang, Fang; Lin, Dunmei; Li, Wei; Dou, Pengpeng; Han, Le; Huang, Mingfen; Qian, Shenhua; Yao, Jingmei
Abstract: Litter decomposition, a fundamental process of nutrient cycling and energy flow in freshwater ecosystems, is driven by a diverse array of decomposers. As an important component of the heterotrophic food web, meiofauna can provide a trophic link between leaf‐associated microbes ( i.e ., bacteria and fungi)/plant detritus and macroinvertebrates, though their contribution to litter decomposition is not well understood. To investigate the role of different decomposer communities in litter decomposition, especially meiofauna, we compared the litter decomposition of three leaf species with different lignin to nitrogen ratios in litter bags with different mesh sizes (0.05, 0.25, and 2 mm) in a forested stream, in China for 78 days. The meiofauna significantly enhanced the decomposition of leaves of high‐and medium‐ quality, while decreasing (negative effect) or increasing (positive effect) the fungal biomass and diversity. Macrofauna and meiofauna together contributed to the decomposition of low‐quality leaf species. The presence of meiofauna and macrofauna triggered different aspects of the microbial community, with their effects on litter decomposition varying as a function of leaf quality. This study reveals that the meiofauna increased the trophic complexity and modulated their interactions with microbes, highlighting the important yet underestimated role of meiofauna in detritus‐based ecosystems. Abstract : Effects of meiofauna on litter decomposition were estimated. Increasing trophic complexity leads to increased decomposition rate. Meiofauna significantly affected fungal biomass and diversity, and the biotic interactions were leaf species dependent.